2012
DOI: 10.1186/1756-0500-5-290
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and considerations among caregivers of a child with autism in Qatar

Abstract: BackgroundAutism impacts the lives of the family looking after a child with the condition in different ways, and forces family members to modify their daily lives to suit their reality. To our knowledge, no previous research investigated concern and considerations of parents/caregivers of children with autism in Qatar or the Arabic speaking Middle Eastern region.MethodsCaregivers of a child who was between the age of 3 to17 years old at the time of the study and who was diagnosed with ASD (Autistic Group or AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Studies have concluded expenses of families for children with ASD are up to three times more than typically developed kids as well as mentally and physically disabled children at the same age. [ 25 ] For participants, treatment costs and lack of insurance support were the biggest financial challenges. Sharp argues in his study that even if insurance companies cover medical tests related to diagnosis, they never pay for therapies for behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have concluded expenses of families for children with ASD are up to three times more than typically developed kids as well as mentally and physically disabled children at the same age. [ 25 ] For participants, treatment costs and lack of insurance support were the biggest financial challenges. Sharp argues in his study that even if insurance companies cover medical tests related to diagnosis, they never pay for therapies for behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, families, professionals and organizations are struggling with financial problems. In Iran, the value of the national currency has declined over the years for various reasons (Mosavi et al , 2018) and, like all Iranian families, it has affected families of children with autism even more severely, because according to studies in the Middle East, 70% of an employee's income is spent on the care of an autistic child (Kheir et al , 2012). As Weiss et al .…”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, we have been especially interested in the quality of life for individuals on ASD spectrum, and those caring for them. 7,8 A major component of the quality of life of any individual is having a healthy life and receiving quality care from all health care providers with no health disparities. Logically, the first step of this effective unbiased health care plan is appropriate communication, which is by definition, the form of a transfer and exchange of information that helps both sender and recipient get a better understanding of the other in order to meet that person's needs or wants.…”
Section: Introductionmentioning
confidence: 99%